Laparoscopic Radical Nephrectomy: The New Gold Standard Surgical Treatment for Localized Renal Cell Carcinoma - Saadettin Yilmaz Eskicorapci; Dogu Teber; Michael Schulze; Mutlu Ates; Christian Stock; Jens J. Rassweiler (The Scientific World Journal)
We will try to demonstrate that laparoscopic radical nephrectomy could be the new gold standard treatment for renal cell carcinoma with the aid of the current reports exploring the advantages and disadvantages of laparoscopic radical nephrectom overopen surgery.